2023
DOI: 10.1111/jgh.16169
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazan poses no additional risk of developing Clostridioides difficile infection compared to proton pump inhibitors

Abstract: Background and Aim The use of proton pump inhibitors (PPIs) has been repeatedly reported as a trigger of Clostridioides difficile infection (CDI), a leading cause of nosocomial diarrhea. However, only a few studies have reported on the association between vonoprazan, a novel potassium‐competitive acid blocker providing potent acid suppression, and CDI, with no studies having been conducted in a clinical setting. We therefore evaluated the association between various classes of acid suppressants and CDI with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Although previous studies found that vonoprazan and PPIs use was positively associated with CDI, the association between vonoprazan and CDI is not beyond that of PPIs use. 36 , 37 However, previous findings have contradicted the effects of vonoprazan on the gut microbiome. 34 In this study, CDI signals were detected for both vonoprazan and PPIs, and the results of the ROR for the suspected drug calculated from the two databases showed that the ROR for vonoprazan was significantly greater than that of PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies found that vonoprazan and PPIs use was positively associated with CDI, the association between vonoprazan and CDI is not beyond that of PPIs use. 36 , 37 However, previous findings have contradicted the effects of vonoprazan on the gut microbiome. 34 In this study, CDI signals were detected for both vonoprazan and PPIs, and the results of the ROR for the suspected drug calculated from the two databases showed that the ROR for vonoprazan was significantly greater than that of PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…This was a secondary analysis of a retrospective hospital-based cohort study in Japan. Details of the original study have been published elsewhere [5]. Briefly, we extracted data of all adult patients who were hospitalized to Akita City Hospital for ≥7 days between January 2016 and December 2020.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Nonsurvivors showed significantly higher rate of severe CDI (54.2% vs. 25.0%, p = 0.012) than survivors. Notably, non-survivors had significantly higher proportion of patients with high risk in the BC category and marginally higher CCI than survivors (83.3% vs. 48.7%, p = 0.004; 4 [2][3][4][5] vs. 2 [1][2][3][4], p = 0.054), while there were no significant differences in the remaining factors (Table 3).…”
Section: Logistic Regression Analyses On Risk Factors Of Developing CDImentioning
confidence: 99%
See 1 more Smart Citation